Major abdominal surgery for Jehovah's Witnesses: Challenge while practicing bloodless medicine in a middle income country - Gavrilovska Brzanov, Aleksandra; Darko DJambaz; Nikola Brzanov; Naumovski, Filip; Sivevski, Atanas; Jovanovski Srceva, Marija; Kuzmanovska, Biljana (SAGE Publications Ltd., 2023)
We present a 59-year-old female Jehovah's Witness patient transferred from another facility to our tertiary center as an emergency case owing to anemia due to gastrointestinal bleeding. A computed tomography scan and gastroscopy confirmed an invasion of the duodenum by a malignant process. The patient underwent a Whipple procedure and a right hemicolectomy refusing blood transfusion. On the 17th postoperative day, the patient was discharged following a successful surgery. This article's objectives are to first highlight the moral and ethical quandary and then share our surgical experiences with this particular patient population. In conclusion, Jehovah's Witnesses' management of major abdominal surgery poses considerable clinical, moral, and legal difficulties. Despite them, doctors must put the patients' needs first while also honoring their religious convictions. However, urgent situations continue to arise, forcing medical professionals to weigh their religious convictions against the need to save a patient's life.